Biomimetic apatite formation on Ultra-High Molecular Weight Polyethylene (UHMWPE) using modified biomimetic solution - Aparecida, Anahi H. [UNESP]; Fook, Marcus V. L.; Guastaldi, Antonio Carlos [UNESP] (Springer, 2009)
Modifications were performed on a biomimetic solution (SBF), according to previous knowledge on the behavior of ions present in its composition, in order to obtain apatite coatings onto Ultra-High Molecular Weight Polyethylene (UHMWPE) without having to use polymer pre-treatments that could compromise its properties. UHMWPE substrates were immersed into a 30% H(2)O(2) solution for a 24-h period and then submitted to a biomimetic coating method using standard SBF and two other modified SBF solutions. Apatite coatings were only obtained onto UHMWPE when the modified SBF solutions were used. Based on these results, apatite coatings of biological importance (calcium-deficient hydroxyapatite-CDHA, amorphous calcium phosphate-ACP, octacalcium phosphate-OCP, and carbonated HA) can be obtained onto UHMWPE substrates, allowing an adequate conciliation between bonelike mechanical properties and bioactivity.